Preparation of edible film from sweet potato peel polyphenols: application in fresh fruit preservation - Zhang, Zhenlin; Wang, Yanhong; Fang, Xingtang; Chen, Xi; Yin, Zhichao; Zhang, Chunlei (Frontiers in Sustainable Food Systems, 2024)
A bioactive composite film, composed of sweet potato peel polyphenols extract and sweet potato starch (SPS), was prepared. The study investigated the influence of various levels of sweet potato peel polyphenols on the physicochemical properties and functional characteristics of the composite film. By uniformly dispersing 0.4% of sweet potato peel polyphenols in the SPS matrix, a homogeneous thin film with enhanced mechanical properties was obtained. The starch-based sweet potato peel polyphenols film exhibited excellent UV barrier properties, improved water and gas barrier properties, and strong antioxidant activity, with clearance rates above 90% for DPPH and ABTS radicals. It also displayed effective antimicrobial abilities against Bacillus subtilis, Escherichia coli, and Staphylococcus aureus. Food packaging experiments revealed that this active composite film slowed the spoilage of fresh cherry tomatoes, extending their shelf life to 7 days when stored at 4°C. Therefore, the developed starch-based sweet potato peel polyphenols composite film holds great potential as an eco-friendly food packaging material with broad application prospects.